A model compound for pyridinechalcone-based multistate systems. Ring opening-closure as the slowest kinetic step of the multistate - Camuenho, Ambrósio (2019)
UID/QUI/50006/2019. PTDC/QEQ-QFI/1971/2014. PTDC/QUI-COL/32351/2017. PTDC/QUI-QFI/30951/2017. grant no. 219201.